Evaluation of synthetic hexaploid wheat (Triticum aestivum) derived RILs for kernel traits - JADON, VASUDHA; DIXIT, DEEPSHIKHA; JAYARAMAN, KARIKALAN; PANDA, KUSUMA KUMARI; SHARMA, SHASHI; KRISHNA, HARI; SINGH, PRADEEP KUMAR; KRISHNAPPA, GOPALAREDDY; SINGH, GYANENDRA PRATAP (The Indian Journal of Agricultural Sciences, 2022)
In bread wheat (Triticum aestivum L.), kernel parameters are significant grain quality characteristics that affect yield and milling quality as well as market price. Utilization of synthetic hexaploid donor to harness the diverse alleles for broadening the genetic base is a novel breeding strategy of the bread wheat breeding programs across the globe. An experiment was conducted during winter (rabi) season 2017–18 and 2018–19 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to evaluate 188 recombinant inbred lines (RILs) which were derived from HD 2932 (Indian bread wheat cultivar) and Synthetic 46 (Syn 46: Synthetic hexaploid donor) to identify the effect of the synthetic hexaploid donor on kernel parameters. Kernel parameters like kernel length (KL), kernel width (KW), kernel thickness (KT) and thousand kernel weight (TKW) were studied. Syn 46 had larger kernels and a high TKW with respect to HD 2932. Significant variation for all the traits was observed in the population with transgressive segregants. In this RILs population (188) KL ranged from 5.13–7.5 mm, KW ranged of 2.26–3.9 mm, KT ranged from 2.57–3.41 mm, and of TKW ranged from 25.2–53.17 g. Correlation analysis showed a significant positive correlation of TKW with KL and KT. Potential RILs identified with desirable allelic combinations may be used for future breeding programs, and RILs with contrasting kernel parameters may be used to create nested RILs for further generation of variability.